Determinantes da estrutura de capital e da velocidade de ajuste em empresas brasileiras - Mitushima, Alexandre Hiroshi (2009)
The study of capital structure is one of the main issues in Corporate Finance. Many researchers, in opposition to the propositions of Modigliani and Miller (1958), suggest that there is an optimal debt-equity ratio. Some authors say that the capital structure has a dynamic behavior and try to build models to identify the determinants of this dynamic capital structure. Some recent papers try to identify the variables that influence the speed of adjustment of capital structure. The objective of this research is to identify the determinants mentioned above in Brazilian companies, by analyzing the financial statements of companies listed in São Paulo Stock Exchange. The academic relevance of this study is to give an overview of the behavior of Brazilian companies regarding their optimal capital structure finding some information that can contribute to future researches.